2016
DOI: 10.3389/fphys.2016.00293
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibition Exerts Renoprotective Effects in Rats with Established Heart Failure

Abstract: Circulating dipeptidyl peptidase IV (DPPIV) activity is associated with worse cardiovascular outcomes in humans and experimental heart failure (HF) models, suggesting that DPPIV may play a role in the pathophysiology of this syndrome. Renal dysfunction is one of the key features of HF, but it remains to be determined whether DPPIV inhibitors are capable of improving cardiorenal function after the onset of HF. Therefore, the present study aimed to test the hypothesis that DPPIV inhibition by vildagliptin improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…DPP‐4 inhibitors improve endothelial dysfunction, blunt inflammation and are efficient in cardiovascular and renal protection. Inflammation takes part and promotes progression of cardiovascular and renal diseases Cellular and molecular mechanisms and pathways of anti‐inflammatory activity of clinically used DPP‐4 inhibitors in cardiovascular and renal protection include the impacts on pro‐ and anti‐inflammatory mediators, cytokines, chemokines, immune cells, cell adhesion molecules, enzymes, transcription factors, pro‐ and antiapoptotic mediators, oxidative stress markers and antioxidative enzymes, receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DPP‐4 inhibitors improve endothelial dysfunction, blunt inflammation and are efficient in cardiovascular and renal protection. Inflammation takes part and promotes progression of cardiovascular and renal diseases Cellular and molecular mechanisms and pathways of anti‐inflammatory activity of clinically used DPP‐4 inhibitors in cardiovascular and renal protection include the impacts on pro‐ and anti‐inflammatory mediators, cytokines, chemokines, immune cells, cell adhesion molecules, enzymes, transcription factors, pro‐ and antiapoptotic mediators, oxidative stress markers and antioxidative enzymes, receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Continued evaluation of these hypoglycemic agents in longer‐term controlled trials on efficacy and safety, as well as clinical practice, are required to assess their profiles, advantages or disadvantages among the current therapies . Apart from diabetes, it has been reported that inhibitors of DPP‐4 are efficient in cardiovascular and renal protection . Cardiovascular safety of sitagliptin, linagliptin, and alogliptin in patients was confirmed in some pooled analysis and studies, but there are others pointing out enhanced risk of heart failure in diabetic patients in long‐term therapy with DPP‐4 inhibitors, with yet unexplained clear cause–effect relationship .…”
Section: Introductionmentioning
confidence: 99%
“…Oral administration of 400 mg dutogliptin inhibited DPP‐IV activity by approximately 85%, but led to lower plasma concentrations compared to parenteral application. We can only speculate as to whether local tissue DPP‐IV inhibition increases with plasma concentration, which might be warranted for improved cardiomyocyte recruitment, as has been suggested by preclinical models investigating vildagliptin . However, it needs to be determined how plasma and tissue concentrations of DPP‐IV activity are related.…”
Section: Discussionmentioning
confidence: 99%
“…In preclinical models of heart failure, high dose, but not low dose, administration of DPP‐IV inhibitors protected renal and improved cardiac function . This leads to the question of whether a parenteral drug formulation providing 100% bioavailability translating into continuously high DPP‐IV inhibition is possibly required to provide modulation of the SDF‐1/CXCR4 axis including these beneficial effects on cardiac remodelling.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the lack of vildagliptin-induced cardioprotection in this study is most likely attributed to the low dose and frequency of administration of vildagliptin employed (once-daily vs. twice-daily dosing frequency). Indeed, we have found that chronic treatment with high (120 mg/day given twice per day) but not low-dose (20 mg/kg given once a day) vildagliptin is capable of ameliorating cardiac and renal function and reducing pulmonary congestion in rats with established HF [ 140 ].…”
Section: Dppiv Inhibitors and Hf: Preclinical Studiesmentioning
confidence: 99%